Efektivitas Suplementasi Lutein dan Zeaxanthin terhadap Perkembangan Atrofi Geografis dan Ketajaman Penglihatan pada Degenerasi Makula Terkait Usia: Tinjauan Sistematis Berdasarkan Uji Klinis: Tinjauan Sistematik - Kesumaputri, Komang Diah Kurnia; Dwipayani, Ni Made; Wibawa, I Made Dwi Surya; Agrasidi, Putu Anindya; -, Felicia (Cermin Dunia Kedokteran, 2026)
Introduction: Geographic atrophy (GA) is an advanced form of dry age-related macular degeneration (AMD) that can cause severe central vision loss if its progression extends to the foveal area. Currently, therapeutic options for GA remain limited, with safety profiles requiring further evaluation. Lutein and zeaxanthin, as the main components of the Age-Related Eye Disease Study (AREDS2) formula, have become the focus of current research. Both are antioxidants concentrated in the macula, which exert protective effects on retinal structures and reduce oxidative stress. This systematic review aims to evaluate the effectiveness of oral lutein and zeaxanthin supplementation on GA progression and visual acuity in AMD patients. Methods: Literature searches were conducted across four biomedical databases based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. A total of four studies met the inclusion criteria and were analyzed qualitatively. Results: The analysis showed that oral supplementation of lutein (10 mg/day) and zeaxanthin (2 mg/day) may reduce the progression of non-central GA and stabilize or improve visual acuity in patients with AMD. Lutein at doses of 10 mg and 20 mg demonstrated similar effectiveness in improving visual acuity through an increase in macular pigment optical density (MPOD). Conclusion: Based on the findings of this systematic review, oral supplementation with lutein (10 mg/day) and zeaxanthin (2 mg/day), as incorporated in the AREDS2 formulation, appears to slow the progression of non-central GA and preserve foveal integrity (foveal sparing). Further long-term studies are required to confirm the clinical benefits and long-term safety.